Calculation of Star Proportion of Green Buildings: A Case Study on GM New District. Issue 3 (1st September 2017) - Hong, Ren; Runyuan, Wang; Yongjie, Du
Abstract : In the context of exploring and implementing China's new urbanization, green eco-city have become a transformation model for urban development. Sharpening green buildings in the construction industry can significantly influence and determine China's economic growth trends, as well as the growth and overall development of its national economy. However, current green eco-city still lack appropriate standards and scientific theoretical basis to determine the target star program of green buildings. To fully implement the green building standards, establish and improve a sound technical standard system for the construction of green building demonstration areas, this study considers the spatial layout of green buildings as the core, adopts a plot potential evaluation method for evaluating a few green building plots, and utilizes four factors in verifying plots with great star potential. The study also establishes a system to calculate the star proportion of green buildings and applies the system in calculating the green building ratio of GM New District. Results indicate that the system can quantitatively analyze a plot potential, calculate the star proportion of green buildings scientifically and rationally, and provide some references for the construction of eco-city and the preparation of special planning for green buildings. The system construction is conducive to provide technical support for the construction of green eco-city. The improved system can be applied in the green building demonstration areas in China, and will be a reference model of constructing green building demonstration areas in the country.